Nano-sized Droplets of Self-Emulsifying System for Enhancing Oral Bioavailability of Chemotherapeutic Agent VP-16 in Rats: A Nano Lipid Carrier for BCS Class IV Drugs - Khalid, Nayab; Sarfraz, Muhammad; Arafat, Mosab; Akhtar, Muhammad; Löbenberg, Raimar; Ur Rehman, Nisar (Journal of Pharmacy & Pharmaceutical Sciences, 2018)
PURPOSE: The purpose of this study was to investigate the ability of a self-nano-emulsifying drug delivery system (SNEDDS) to enhance the oral bioavailability of a BCS class IV drug, etoposide (VP-16). METHOD: A series of SNEDDS formulations with VP-16 were prepared consisting of medium chain triglycerides, polysorbate 80, diethylene glycol monoethyl ether and propylene glycol monolaurate type-1. Based on an obtained ternary phase diagram, an optimum formulation was selected and characterized in terms of size, zeta potential, loading, morphology and in vitro drug release. The pharmacokinetic parameters and oral bioavailability of VP-16 suspension and VP-16 in SNEDDS was assessed using 30 Male Sprague–Dawley rats and compared with the commercial product (VePesid®). RESULTS: Pharmacokinetic data showed that the mean values for AUC0-t of VP-16 in SNEDDS was 6.4 fold higher compared to a drug suspension and 2.4-folds higher than VePesid®. Similarly, the mean value for Cmax of VP-16 in SNEDDS (1.13± 0.07 µg/ml µg.h/mL) was higher than VePesid® (0.62± 0.09 µg/mL) and drug suspension (0.13± 0.07 µg/mL). CONCLUSION: The SNEDDS formulation was able to enhance the oral bioavailability of the BCS Class IV chemotherapeutic agent VP-16 by increasing the dissolution and absorption of the drug. A good in vitro in vivo correlation was found between the in vitro dissolution and in vivo absorption data of VP-16 SNEDDS preparation. Therefore, SNEDDS formulations might be a very promising approach for BCS Class IV drugs.